Pengaruh Pertumbuhan Perusahaan dan Kemampuan Good Corporate Governance Terhadap Pengungkapan Akuntansi Karbon - Anjilni, Ratih Qadarti; Asih, Fitria Kinanthi (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to analyze and obtain empirical evidence regarding the Effect of Company Growth and Good Corporate Governance Capabilities on Carbon Accounting Disclosures. The approach used in this study is a quantitative approach with associative methods. The data used in this study is secondary data obtained from the company's annual report (Annual Report) and sustainability report (Sustainability Report) obtained through the official website of the Indonesia Stock Exchange (IDX) and the official website of each company. The sample used in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021, totaling 6 companies. The sampling technique in this study used a purposive sampling method. In this study using descriptive statistical analysis techniques, panel data regression test, model test. classic assumption test and hypothesis test using data processing program Eviews version 12. The results of this study indicate that Company Growth and Good Corporate Governance Capabilities simultaneously affect Carbon Accounting Disclosures, while partially Company Growth has no effect on Carbon Accounting Disclosures, Institutional Ownership and Audit Committee affect Carbon Accounting Disclosures